Preparation of Ni(OH)2 nanoplatelet/electrospun carbon nanofiber hybrids for highly sensitive nonenzymatic glucose sensors. Issue 31 (31st March 2017) - Chen, Linlin; Liu, Lijuan; Guo, Qiaohui; Wang, Zhonghui; Liu, Guiling; Chen, Shuiliang; Hou, Haoqing
Abstract : Ni(OH)2 nanoplatelets anchored on electrospun carbon nanofibers lead to excellent glucose biosensing. Abstract : Ni(OH)2 nanoplatelet/electrospun carbon nanofiber (ECF) hybrids have been simply prepared for the construction of nonenzymatic glucose biosensors. The resulting Ni(OH)2 /ECF hybrids were carefully examined using SEM, TEM, HRTEM, XRD, and XPS. For all hybrids, two-dimensional Ni(OH)2 nanoplatelets were uniformly anchored on the one-dimensional ECFs, forming a hierarchical nanostructure, and the thickness of Ni(OH)2 nanoplatelets could be readily tailored by controlling the content of Ni(OH)2 precursor. Cyclic voltammetric studies showed enhanced redox properties for Ni(OH)2 /ECF-based electrodes relative to pure Ni(OH)2 nanoplatelet electrode and significantly improved the electrocatalytic activity for glucose oxidation. The application of Ni(OH)2 /ECF-based electrodes to glucose detection was explored. A low limit of detection (0.1 μM), wide detection linear range (0.005–13.05 mM), and excellent signal stability and reproducibility were demonstrated by this novel Ni(OH)2 /ECF-0.06 hybrid. The sensor was also applied in real serum samples, giving satisfactory results. The simple preparation, low cost, and enhanced electrocatalytic performance of these hybrids could pave the way for highly sensitive glucose sensors.